The Role of Contrastive Analysis in Foreign Language Teaching_From the Point of View of French and English language Professors - Messaoudani, Sara; Mecili, Ouarda (Milev Journal of Research and Studies, 2021)
The subject of teaching and teaching foreign languages ​​is one of the most important issues that preoccupied researchers in the past and present, in which thinkers of different intellectual and scientific specializations have researched. Contrastive analysis is one of the most important curricula that had a significant impact on the preparation of curricula for teaching foreign languages. The contrastive analysis approach is one of the most important approaches that had a significant impact in the preparation of curricula for teaching foreign languages, and which proved its effectiveness in teaching languages, and from this point of view and given the importance of teaching and learning languages, we will try through this research paper to reveal the effectiveness of contrastive analysis in teaching languages. The foreign language, by going to the field and questioning the professor of French and English about the importance of this approach in teaching and learning a foreign language within the department, and the extent to which the learner and teacher employ the language interview in learning and teaching a foreign language.